2009
DOI: 10.1007/s12291-009-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid a better scavenger of free radicals than vitamin C in rheumatoid arthritis

Abstract: Uric acid an endogenous aqueous antioxidant in normal humans is present in much higher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“…RA patients in our study showed statistically significant increased serum uric acid level when compared with healthy controls as given in Table 1. This finding is in accordance with the Mahajan et al 26 The increased level of uric acid shows that it contributes to scavenging the free radicals. 27 Increased uric acid level in RA patients may be a compensatory response to combats the low levels of major non-enzymatic antioxidants like vitamin C and E.…”
Section: Discussionsupporting
confidence: 92%
“…RA patients in our study showed statistically significant increased serum uric acid level when compared with healthy controls as given in Table 1. This finding is in accordance with the Mahajan et al 26 The increased level of uric acid shows that it contributes to scavenging the free radicals. 27 Increased uric acid level in RA patients may be a compensatory response to combats the low levels of major non-enzymatic antioxidants like vitamin C and E.…”
Section: Discussionsupporting
confidence: 92%
“…The same result was reported by [18]. This increase in uric acid level which may refer to the physiological activity and the influence of destroyed or catabolism [19].Increased level of uric acid may contribute much more to scavenging of free radicals. This may support the powerful antioxidant role of uric acid in scavenging singlet oxygen and other free radicals [20] and [21].…”
Section: Discussionsupporting
confidence: 81%
“…As urate was previously reported to act as a pro-oxidant under some conditions [13] , we also studied the effect of urate on oxidative stress by determining the protein oxidation product carbonyl levels. We found that 50 µmol/l 6-OHDA treatment enhanced the cellular protein carbonyl levels, which was obviously attenuated in the presence of 200 µmol/l urate pretreatment.…”
Section: Resultsmentioning
confidence: 99%